Anxiety and Depression Symptoms in a General Population and Future Risk of Bloodstream Infection: The HUNT Study. Issue 7 (September 2018) - Askim, Åsa; Gustad, Lise Tuset; Paulsen, Julie; Reitan, Solveig Klæbo; Mehl, Arne; Mohus, Randi Marie; Dewan, Andrew; Damås, Jan Kristian; Solligård, Erik; Åsvold, Bjørn Olav
ABSTRACT: Objective: We examined whether anxiety and depression symptoms constitute increased risk of bloodstream infection (BSI), as a proxy for sepsis. Methods: A general population with self-reported anxiety and depression symptoms was followed prospectively for hospital-verified BSI. Using multivariable Cox regression analysis, we estimated hazard ratios (HR) with 95% confidence intervals (CI) of BSI and BSI mortality, with and without statistical adjustment for comorbidities, BMI, and life-style factors that may confound or mediate the associations. Results: During 14.8 years median follow-up of 59, 301 individuals, 1578 (2.7%) experienced BSI and 328 (0.55%) participants died within 30 days after a BSI. Severe depression symptoms were associated with a 38% increased risk of BSI, adjusted for age, sex, and education (HR = 1.38, 95% CI = 1.10–1.73). The HR was attenuated to 1.23 (0.96–1.59) after adjustment for comorbidities and to 1.15 (0.86–1.53) after additional adjustment for BMI and life-style factors. For severe anxiety symptoms, the corresponding HRs were 1.48 (1.20–1.83), 1.35 (1.07–1.70), and 1.28 (0.99–1.64). Moderate symptoms of depression and anxiety were not associated with increased BSI risk. The analysis of BSI mortality yielded imprecise results but suggested an increased risk of BSI mortality in participants with moderate depression symptoms. Conclusions: Severe depression and anxiety symptoms were associated with a moderately increased risk of BSI. The association may, at least in part, be confounded or mediated by comorbidities, BMI, and life-style. Future research should investigate whether interventions targeting improved BMI and life-style may reduce the risk of BSI and sepsis in people with depression and anxiety symptoms. Abstract : Supplemental digital content is available in the text.